The Effect Communication Strategy and Training on Social Awareness of Generation Z - Rizky, M. Chaerul; Salma, Cantika Dwi (LifeSciFi, 2025)
This research is motivated by the low social awareness among Generation Z which is a serious concern. The lack of effective communication strategies and the lack of relevant training are the main factors that exacerbate this condition. The purpose of this study is to analyze the influence of communication strategies and training on the social awareness of Generation Z. This study uses a quantitative approach with a correlational type. The population of Sei Dendang Village is recorded at 292,951 people, and the sample used in this study is 30 people from Generation Z. Data were collected using a closed questionnaire based on indicators of communication strategies, training, and social awareness. The results show that communication strategies and training simultaneously and partially have a positive and significant effect on the social awareness of Generation Z. Digital and interactive communication strategies can increase social understanding and awareness, while training relevant to social values ​​strengthens empathy and collective responsibility. These findings provide an important basis for youth empowerment program designers to develop technology-based approaches and participatory training to increase their social engagement in the community.